The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1017/s0043174500079066
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Monoecious and Dioecious Hydrilla (Hydrilla verticillata) Biotypes

Abstract: Selected biological and physiological parameters of hydrilla [Hydrilla verticillata(L.f.) Royle # HYLLI] biotypes were compared in growth chambers, glasshouse, or outside aquaria. Salinity tolerance was similar for both biotypes with an injury threshold of approximately 13 parts per thousand (ppt). The registered aquatic herbicides diquat (6,7-dihydrodipyrido [1,2-α:2′,1′-c] pyrazinediium ion) and dipotassium and monoamine salts of endothall (7-oxabicyclo [2.2.1] heptane-2,3-dicarboxylic acid)4produced similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 12 publications
5
34
1
Order By: Relevance
“…The general pattern in this experiment agrees with that noted previously by other researchers (Hailer et aL 1976, Van et al 1978, Bowes et al 1979, Spencer and Anderson 1986, 1987, Steward and Van 1987, Van 1989. Propagule production is enhanced by short photoperiod and reduced by long photoperiod.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The general pattern in this experiment agrees with that noted previously by other researchers (Hailer et aL 1976, Van et al 1978, Bowes et al 1979, Spencer and Anderson 1986, 1987, Steward and Van 1987, Van 1989. Propagule production is enhanced by short photoperiod and reduced by long photoperiod.…”
Section: Discussionsupporting
confidence: 92%
“…Previous reports have demonstrated that photoperiod (HalIer et al 1976, Van et al 1978, Bowes et al 1979, Spencer and Anderson 1986, 1987, Steward and Van 1987 and soil fertility (Bruner and Batterson 1984, Barko and Smart 1986, McFarland and Barko 1987, Spencer 1990, Spencer et al 1992) influence vegetative 134 propagule production. For many species, interactions between environmental factors and propagule production have not been studied.…”
Section: Introductionmentioning
confidence: 96%
“…Dioecious Hydrilla tubers may not sprout as well at the cooler temperatures (typical of the greenhouse during the periods that the experiments were conducted) as monoecious Hydrilla or Potamogeton propagules (Steward andVan 1987, Madsen andAdams 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal means (April to October) of the measurements were calculated as well as early growing season means. Early growing season was defined by temperature and included data from the first 2 months when temperatures reached 15°C, which is when experiments have shown these freshwater species, particularly H. verticillata, to sprout from tubers or germinate (Carter et al 1994;Steward and Van 1987).…”
Section: Historical Water Qualitymentioning
confidence: 99%